Analisis Strategi Pemasaran untuk Meningkatkan Penjualan pada Toko Sembako di Sape (Studi Kasus pada Toko Sri UD. Laris Manis) - Nur Ayu; Nur Fadilah; Ita Purnama (Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to analyze marketing strategies to increase sales at the Grocery Store in Sape (case study at Sri UD. Laris Manis Store). This study uses a qualitative research method. The subjects of this study are in the marketing analysis section to increase sales. The results of the analysis show that the internal environmental analysis in this internal environmental analysis of the Laris Manis Store in terms of promotion is good but still lacking in promotion through digital media. The products sold are also varied so that consumers who subscribe feel quite satisfied. The persistence in opening a store is also good, but in financial management it has not been implemented properly. And in customer service still needs to be improved. External Environmental Analysis, External environmental conditions that affect the Laris Manis Store are competition between similar trades and the potential for new competitors to enter which causes weaknesses created by existing traders so that many are eyeing the same business and competing in terms of service and social interaction in the fight for consumers.